Researching the mental health needs of hard-to-reach groups: managing multiple sources of evidence - Lamb Jonathan; Kovandzic Marija; Hibbert Derek; Gowers Simon; Gabbay Mark; Clarke Pam; Chew-Graham Carolyn; Catlin Amy; Burroughs Heather; Bower Peter; Aseem Saadia; Edwards Suzanne; et al. (BMC, 2009)
Abstract Background Common mental health problems impose substantial challenges to patients, carers, and health care systems. A range of interventions have demonstrable efficacy in improving the lives of people experiencing such problems. However many people are disadvantaged, either because they are unable to access primary care, or because access does not lead to adequate help. New methods are needed to understand the problems of access and generate solutions. In this paper we describe our methodological approach to managing multiple and diverse sources of evidence, within a research programme to increase equity of access to high quality mental health services in primary care. Methods We began with a scoping review to identify the range and extent of relevant published material, and establish key concepts related to access. We then devised a strategy to collect - in parallel - evidence from six separate sources: a systematic review of published quantitative data on access-related studies; a meta-synthesis of published qualitative data on patient perspectives; dialogues with local stakeholders; a review of grey literature from statutory and voluntary service providers; secondary analysis of patient transcripts from previous qualitative studies; and primary data from interviews with service users and carers. We synthesised the findings from these diverse sources, made judgements on key emerging issues in relation to needs and services, and proposed a range of potential interventions. These proposals were debated and refined using iterative electronic and focus group consultation procedures involving international experts, local stakeholders and service users. Conclusions Our methods break new ground by generating and synthesising multiple sources of evidence, connecting scientific understanding with the perspectives of users, in order to develop innovative ways to meet the mental health needs of under-served groups.